VARIATION IN POINT MUTATIONS OF L -ARABINOSE ISOMERASE Thermotoga thermarum (TTAI) THROUGH THE ANALYSIS OF ENZYME STRUCTURE AND DOCKING SIMULATION - Syahputra, Gita; Kusharyoto, Wien (LIPI Press, 2017)
D-tagatose is one of the products of L-arabinose isomerase which can be applied to food, cosmetics, and health. D-tagatose produced by L-AI has a low quantity. L-AI enzyme from thermophilic bacteria as Thermotoga thermarum (TTAI) can produce higher quantity of D-tagatose than mesophilic bacteria. Point mutation can increase L-AI activity. The analysis of enzyme structure and docking simulation can determine the variation in point mutations. Based on analysis of enzyme structure and docking simulation, TTAI has 494 amino acids compiled by 17 of α-helix dan 18 of β-strand. The analysis of TTAI structure get several active side residues Gln16, Leu18, Tyr19, Phe81, Gln125, His126,Met183, Phe273, Glu300, Glu327, Tyr329, His344, Met345, Ile366, His442, His443. The docking simulation suggested that the residues for binding D-tagatose are Trp422 and Tyr331. Two point mutations, i.e. M183A and F273L, are recommended based on the analysis of TTAI structure, homology structure, residues, and docking simulation. This variation in mutation can be used for further research in vitro.